Energy expenditure measured with accelerometers and self-report questionnaire in people with intellectual disabilities - Pérez-Cruzado, David Francisco; Cuesta-Vargas, Antonio (Wiley, 2018)
Background There are different instruments to measure energy expenditure in general population, but we do not know whether these instruments can be used in people with intellectual disability. Methods A sample of 33 participants was invited to wear a triaxial accelerometer during seven consecutive days. Energy expenditure was measured with the International Physical Activity Questionnaire Short Version (IPAQ-S) to gather data regarding the participant's descriptions of the physical activity performed. Results Agreement between the accelerometers and IPAQ-S in terms of energy expenditure measurements was not reached (P > 0.05). A significant correlation was found between moderate metabolic equivalent of tasks measured with accelerometers and vigorous metabolic equivalent of tasks measured with the IPAQ-S (r = −0.351 [P = 0.045]). Conclusion The main conclusion of this study was a level of discrepancy between measurements taken using the IPAQ-S and the accelerometers in people with intellectual disability.
Keywords: Ejercicio físico; Deficiencia mental; Acelerometria; Actividad fisica; Discapacidad intelectual